Determinación de la presencia del virus de newcastle e influenza aviar en aves de traspatio de la provincia de Loja. - Gaona Castillo, Nixon Hernan (2017)
Avian Influenza and Newcastle disease are highly contagious diseases affecting many species of poultry causing high mortalities. This research study was carried out in Loja Province, South of Ecuador, with the purpose of determining the presence of the Newcastle (NC) and Avian Influenza (AI) virus, so 300 samples were collected of fresh stool and swab sewage of backyard poultry and cockfight birds that can be found near wetlands and commercial poultry for viral isolation in laboratory. These data was loaded to an academic software ARCGIS, updating data of wetland sites of industrial poultry production, access roads, thus achieving in this way represent the area of interest as a map with their respective symbols expressed in geo-referenced sampling points. Besides, the collected samples came from healthy birds and birds with signs of the disease or symptoms of respiratory and digestive illness, being the largest number of samples of healthy birds allegedly not vaccinated for NC, the viral isolation was performed in 9 to 11 days in embryonated eggs. Also, it was used the allantoic fluid of the inoculated eggs to the hemagglutination test to determine the presence of the virus. The results of laboratory tests were negative, in the viral isolation and Haemagglutination test did not show disease of NC or AI virus (0/300), with a prevalence of 0(0-1,19), the confidence interval was 95%. Therefore, it is concluded that the sampled birds in Loja province were not infected by these viruses of Newcastle and Avian Influenza. Key words: Virus, Newcastle, Avian Influenza, viral isolation.